Relationship of body mass index with bone mineral density in postmenopausal women: an Indian perspective - Goyal, Avani; Malla, Veena Ganju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Osteoporosis is a common health problem that affects postmenopausal females, leading to increased susceptibility to fractures. Body mass index (BMI) has been shown to be an important predictor of bone mineral density (BMD) with increased body weight correlating with positive influence on bone metabolism. Low BMI predisposes postmenopausal females to rapid bone loss and low bone mass, crucial in the pathogenesis of osteoporosis. However, a specific BMI value chart to accurately predict osteoporosis remains to be fully established. The present study aimed to investigate the relationship of BMI and BMD in postmenopausal Indian females. Methods: 90 healthy postmenopausal females with 1-5 years of menopause were enrolled in the study. Subjects were categorized according to their BMI into normal, overweight and obese. BMD was assessed using dual energy X-ray absorptiometry (DEXA) scan at L1-L4 vertebrae and femoral neck and expressed as T-scores. Quantitative variables were compared using ANOVA/Kruskal Wallis Test. Results: Bone mineral density was significantly higher in the obese group as compared to normal BMI group at both lumbar spine (p=0.001) and femoral neck (p=0.001). BMD at lumbar spine was lower than that at femoral neck across all the three groups of BMI. Conclusions: BMI and body weight are important factors affecting BMD. Postmenopausal females with low BMI are more likely to have osteopenia and osteoporosis and are thus at an increased risk of pathological fractures. Routine BMD monitoring in postmenopausal females with low BMI may be necessary to initiate early clinical interventions for osteoporosis.